SISTEM INFORMASI KEPEGAWAIAN BERBASIS WEBSITE PADA PT. KURNIA PERSADA MITRA MANDIRI - Novita Chandra; Dafid Dafid; Chriestina Chriestina (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
PT Kurnia Persada Mitra Mandiri Palembang is one of the companies engaged in the furniture business established in 2003 that produces three types of products including springbeds, sofas, and foam mattresses. Employment activities are still constrained by the relatively long process of data retrieval, data is difficult to find, data is not integrated, and data recap is often recorded repeatedly. The system development method used in writing this script is the waterfall method, while for website creation using PHP, HTML, CSS, Javascript, servers use XAMPP and MySQL as databases. The result is to build a website-based employment information system that can help and facilitate the management of employment data.